Transgenic Eimeria magna Pérard, 1925 Displays Similar Parasitological Properties to the Wild-type Strain and Induces an Exogenous Protein-Specific Immune Response in Rabbits (Oryctolagus cuniculus L.) - Tao, Geru; Shi, Tuanyuan; Tang, Xinming; Duszynski, Donald W.; Wang, Yunzhou; Li, Chao; Suo, Jingxia; Tian, Xiuling; Liu, Xianyong; Suo, Xun (Frontiers in Immunology, 2017)
Rabbit coccidiosis causes great economic losses to world rabbitry. Little work has done using genetic manipulation on the etiological agents, rabbit Eimeria spp. In this study, we constructed a transgenic line of E. magna (EmagER) expressing enhanced yellow fluorescent protein (EYFP) and red fluorescent protein (RFP) using regulatory sequences of Eimeria tenella and Toxoplasma gondii. We observed the life cycle of EmagER and confirmed that the transgenic parasites express exogenous proteins targeted to different cellular compartments throughout the entire life cycle. EYFP was expressed mainly in the nucleus, and RFP both in the nucleus and cytoplasm. Coccidia-free, laboratory-reared 35-day-old rabbits infected with either EmagER or our wild-type oocysts had identical pre-patent and patent periods and similar oocyst production. Similarly, coccidia-free rabbits inoculated with either transgenic or wild-type oocysts produced statistically significantly fewer oocysts than did unimmunized control rabbits. Finally, we immunized rabbits with transgenic oocysts and found that the they stimulated exogenous, protein-specific immunity in the mesenteric lymph nodes.